Genetic diversity of the genus Citrus in Tomini Bay coastal areas, Indonesia based on morphological characters - NOVRI YOULA KANDOWANGKO; FEBRIYANTI FEBRIYANTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kandowangko NY, Febriyanti. 2023. Genetic diversity of the genus Citrus in Tomini Bay coastal areas, Indonesia based on morphological characters. BIodiversitas 24: 2938-2952. Citrus plants are one of the fruit plants that are widely consumed by the community, both for food, health, and customs. The existence of Citrus plants in the coastal area of Tomini Bay only grows wild and has not been cultivated intensively. Lack of information on the diversity of citrus and the use of Citrus plants that are not balanced with cultivation actions will threaten the existence of these Citrus plants. This research aims to provide information about the morphological characteristics of the genus Citrus in the coastal area of Tomini Bay. The plant materials used were 39 accessions consisting of 7 species. Descriptive methods and diversity index calculations as well as analysis of phenetic consanguinity data were applied in this study. The results showed that all Citrus accessions have morphological diversity ranging from stems, leaves, flowers, fruits, and seeds that are influenced by genetic and environmental factors. The diversity index (H’) was equal to 0.8103 which was categorized as low. The 39 Citrus accessions were divided into two main clusters with a similarity index of 64.3%. The findings of this study are expected to be useful in Citrus breeding and conservation programs in the future.